Seismic waves and rays in elastic media - Slawinski, M. A. 1961- (Pergamon, 2003)
This book seeks to explore seismic phenomena in elastic media and emphasizes the interdependence of mathematical formulation and physical meaning. The purpose of this title - which is intended for senior undergraduate and graduate students as well as scientists interested in quantitative seismology - is to use aspects of continuum mechanics, wave theory and ray theory to describe phenomena resulting from the propagation of waves.The book is divided into three parts: Elastic continua, Waves and rays, and Variational formulation of rays. In Part I, continuum mechanics are used to describe the ma
Keywords: Seismic waves.; Continuum mechanics.; Seismology -- Mathematics.; elektronické knihy; electronic books